KUALIFIKASI PENJARAHAN PASCA GEMPA TSUNAMI DAN LIKUIFAKSI DI KOTA PALU (Suatu Tinjauan Kriminologis) - Kaharuddin Syah (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
Emergencies are not justification for the absence of the state / government handling victims of earthquakes, tsunamis and liquefaction which have destroyed the face of the city of Palu. The state is needed to prepare and buy all the basic needs of food, drinks, clothing, medicines from stores that have the potential to be looted by the people instead of allowing or even encouraging them to collect goods from shops or super markets. The absence of the state in a disaster situation has the potential for chaos. Because fellow nationals are easily ignited by conflicts with all-consuming psychological conditions, it is the state that has to plunder the shops at reasonable prices and then distribute them in an orderly manner to citizens who are in dire need. The norms of criminal law in the disaster country give weight to the perpetrators of looting. The substance of Article 363 paragraph 1 of the Criminal Code regulates that every theft during a natural disaster can be sentenced to a maximum of seven years in prison. The criminal threat is more severe than theft in normal situations. Not yet healed of pain due to the disaster came another disaster because his property was looted by other humans. Even though they have been grateful for being given the opportunity to live.Keyword: Looting, Post Earthquake Tsunami and Liquidation.